Interplay between oxidative stress and physical exercise in hospitalized older adults: a secondary analysis of an RCT using malondialdehyde as a biomarker - Chenhuichen, Chenhui; Azanon-Nogueira, Pedro; Izco-Cubero, Maite; Echeverria-Beistegui, Iciar; Alvarez-Rodriguez, Patricia; Zambom-Ferraresi, Fabíola; Zambom-Ferraresi, Fabricio; Fernández González De La Riva, Marisa; Borrás, Consuelo; Martínez-Velilla, Nicolas (Frontiers in Aging, 2026)
IntroductionOxidative stress, driven by the imbalance between reactive species from oxygen and nitrogen and antioxidant defense mechanisms, plays a pivotal role in aging-related pathologies. Structured multicomponent exercise interventions have mitigated hospital-acquired disability by improving physical and cognitive function and quality of life. However, the underlying molecular mechanisms of this improvement remain partially understood.MethodsWe conducted a secondary analysis of a randomized controlled trial to investigate the impact of a supervised exercise program on oxidative stress in hospitalized older adults. Participants were randomized to a 3-day tailored exercise program based on baseline functional capacity. Serum malondialdehyde (MDA) levels (μmol/mL) and the oxidative oxidation of total proteins (PO) were measured. RESULTS: Seventy-two participants were included in this subanalysis (mean age 86.8 years [SD 4.96], 53.8% female [n = 39]). The exercise group showed a minimal change in MDA levels, while the control group exhibited a significant increase, with a between-group difference of −0.24 μmol/mL (p < 0.01). Subgroup analyses demonstrated significant benefits in patients with diabetes and in women. The intervention improved functional capacity and subjective health status. Participants with lower baseline oxidative stress levels showed greater improvement in SPPB compared to those with higher baseline levels.DiscussionStructured exercise may mitigate the increase in oxidative stress in hospitalized older adults, particularly in women and those with diabetes. The magnitude of functional improvements could depend on baseline oxidative status, highlighting the need for personalized interventions. Future research should explore long-term effects, biomarkers, and tailored protocols to optimize outcomes in this population.